Public prosecution of Ukraine as a special state institute - Москалюк, Юлія Дмитрівна; Литвинюк, Маріанна Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article describe some problems of state regulation of functioning of public prosecution in Ukraine, the interaction of powers between themselves and local prosecutors in the system of separation of powers. In the process of building an independent Ukraine and establishment of constitutional order, the creation of the Constitution of Ukraine gained significant experience with democratic and legal development. In turn, this rapid development of the rule of law, which exists reliable mechanism to ensure and protect the rights and freedoms requires a scientific analysis of the legal status of prosecutors, issues of reform and characteristics of competence, normative basis guarantee activities. Institute prosecution plays a major role in public life. We are inclined to think that given the situation in the country we talk about the functioning of prosecution as an independent government structure which is not subordinate bodies or executive or judicial branches. In Ukraine, the Prosecutor’s Office serves as: maintenance of public prosecution in court; representation of citizens or the state in court in cases determined by law; supervise the observance of laws by bodies that conduct detective and search activity, inquiry and pretrial investigation; supervise the observance of laws in the execution of judgments in criminal proceedings, as well as the application of other measures of coercion related to the restraint of personal liberty of citizens. Under the conditions prevailing in Ukraine, prosecutors from the perspective of law affects all branches of government, what serves as one element of a system of checks and balances. At the same time it promotes interaction between branches of government, because they are interested in keeping and strengthening the rule of law. It is unacceptable, in our opinion, the prosecutor also include one of the three branches of government, as it performs the functions of an entirely different nature. Otherwise we get that in one branch will stay two state-riznofunktsionalnoho character structure that we have today, taking into account recent developments in national legislation of Ukraine.